Identification and functional characterization of conserved promoter elements from glass: A retinal development gene of Drosophila. - Liu, H.; Ma, C.; Moses, K. (Mechanisms of Development, 1996)
The Drosophila melanogaster glass transcription factor acts in photoreceptor cell development, glass transcription in the developing eye begins in the morphogenetic furrow. We report a deletion analysis which shows that a 5147 bp fragment can confer near wild-type expression in the developing eye. We completed the sequence of a similar Drosophila virilis fragment and comparison of these two genomic sequences reveals seven perfectly conserved sequence elements of 15 bp (or longer). We placed oligomers of each element 5' to an hsp70 promoter-lacZ fusion construct, and examined the patterns of beta-galactosidase expression produced in transgenic files. Three of these elements drive beta-galactosidase expression in the developing eye, and one is inhibitory.